Vertebrobasilar Dolichoectasia as A Rare Cause of Trigeminal Neuralgia - A Case Report (Bangladesh Journal of Neuroscience, 2026)
We present a case of 24 years old young male with trigeminal neuralgia due to vertebrobasilar dolichoectasia, a rare condition characterized by enlargement, tortuosity, or elongation of intracranial arteries. Dolichoectatic vessels can cause dysfunction ofcranial nerves through direct vascular compression. Vertebrobasilar dolichoectasia is a rare cause of trigeminal neuralgia and a successful outcome can be achieved with microvascular decompression. The relationships of vertebrobasilar dolichoectasia withthe particularities of neurovascular conflict and images findings are discussed.